GETTING TO KNOW HAJI WAN MOHD. SHAGHIR BIN ABDULLAH - Toguan bin Malim Hasan (IAIN Padangsidimpuan, 2023)
AbstractThe purpose of this writing is to find out the character of Haji Wan Mohd Shaghir bin Abdullah. This research method uses a literature review by collecting documents or archives about this character. The analysis carried out by the researcher is a descriptive analysis. The results of the study show that Tuan Guru Muhatir bin Haji Joll has a scientific sanad that continues with the scholar Sheikh Daud bin Abdullah al-Fathani, namely the Sanad Aqidah Experts Sunnah wal Jama'ah starting from his teacher Sheikh Isa bin Ahmad al- Badawi to Imam Abul Hasan al-Ash'ari. In another recitation, one more sanad goes to Imam Abu Mansur al-Maturidi. His works include 10 works, including the Zuhur Storm, a cluster of beautiful flowers, Sheikh Ahmad al-Fathani volumes 1 and 2, Hadiqatul Azhar war Rayahim, Sheikh Ahmad al-Fathtani,Â Â Â